The Influence of E-Money and Shopee Paylater Usage on Impulse Buying Behavior of Febi UINSU Students: A Review of Maqashid Syariah - Hanafi Nasution, M Mifta; Sugianto, Sugianto; Tambunan, Khairina (Universitas Ibn Khladun Bogor, 2025)
The present research focuses on examining, from the perspective of maqashid sharia, the role of e-money usage and Shopee Paylater on the impulse buying tendencies of FEBI UINSU students. A quantitative approach was employed, using purposive sampling to select 60 respondents. This study aims to examine how the use of e-money and Shopee PayLater influences impulse buying behavior among FEBI UINSU students, while also assessing its implications through the lens of maqashid sharia. Data information gathered through surveys was evaluated using multiple linear regression analysis. The study results show that both e-money and Shopee PayLater have a notable effect on students’ impulse buying tendencies. The result is the use of electronic money positively influences the impulsive buying behavior of FEBI UINSU students. The ease of transactions and attractive promotions offered by electronic money platforms encourage unplanned purchases. Similarly, the use of Shopee PayLater also shows a positive impact on impulsive buying, as its discount features and deferred payment options stimulate greater consumer spending. Furthermore, the combined use of e-money and Shopee PayLater significantly increases students’ tendency toward impulsive purchases. From the perspective of maqasid sharia, this behavior can be assessed through five dimensions: protection of property, intellect, life, lineage, and religion. Impulse buying, particularly when excessive, can result in waste and inefficient use of wealth, which contradicts the Islamic principle of prudent financial management. Moreover, such behavior often overlooks rational decision-making, which should form the basis of consumption choices.